Metabolic syndrome and its relationships with adiponectin, vitamin d and physical activity amongadults in an institute of higher learning in the United Arab Emirates - Hasan , Hayder Abbas (2017)
Metabolic syndrome (MetS) is a cluster of risk factors for cardiovascular disease and type 2 diabetes. It is associated with adipose tissue dysfunction resulting from obesity, an escalating global phenomenon related to lifestyle. Meanwhile,hypovitaminosis D is gaining attention beyond the classical effects on the skeleton. Lifestyle, biochemical and genetic factors are hypothesized to contribute to the pathophysiology of MetS. The aim of this study was to examine the relationships of MetS and its components with adiponectin, vitamin D, VDR gene polymorphisms, and physical activity. The study was conducted from year 2012 until year 2015 in 2 phases (P-1 and P-2). P-1 (cross-sectional): A total of 235 adults (64 males and 171 females) from the University of Sharjah community were recruited. Anthropometric measures, biochemical tests (glucose, insulin, lipid profile, vitamin D and HMW adiponectin) and genetic analyses (for VDR gene polymorphisms: TaqI, FokI, and BsmI) were performed. Demographic profile, habitual dietary intake and exercise perception (Exercise benefits/barriers Scale) were used accordingly. P-2 (interventional): A total of 52 female participants wore pedometers for 9 weeks after an educational session and goal setting of 10,000 steps per day. All baseline parameters were reassessed post-intervention.The prevalence of MetS was 17.5%; higher in males (OR=10.97, 95%CI: 5.1-23.61, p<0.001) and adults above 40 years old (OR=9.59, 95%CI: 3.98-23.1, p < 0.001). HMW adiponectin was higher in females and in those without MetS; being directly correlated with HDL-cholesterol and inversely correlated with obesity measures and blood pressure. Vitamin D level was 22.49(19.6) nmol/L and only 9.8% had an optimal level.Vitamin D was significantly lower in females [26.6(13.58) nmol/L vs. 34.03(21.34) nmol/L, p < 0.001] and in those without MetS [29.6(18.75) nmol/L vs. 21.06(19.1)nmol/L, p < 0.001] than their counterparts. MetS occurrence was independent of vitamin D status (OR=1.78, 95%CI: 0.65-4.84, p=0.25). The three vitamin D receptor gene polymorphisms did not show any relationship with MetS. However, FokI polymorphisms and F allele in females were associated with higher systolic blood pressure. The participants reported exercise perception benefit/barrier ratio of 1.48. The participants walked 7056±1570 steps per day, recording a marginal increase toward the end of week 9. Small, though, significant reductions were noted in almost all anthropometric parameters and LDL-cholesterol (63.8±18.04 mg/dl vs. 59.17±18.61 mg/dl; p=0.01), while an increase of HMW adiponectin (4.08±0.55 μg/ml vs. 4.15±0.53 μg/ml; p = 0.03) was obtained. An inverse relationship between the number of steps and obesity measures, and positive relation with HMW adiponectin level were evident. While the number of steps in normal body mass index (BMI) participants was marginally higher (7488.49±1098) than those with higher BMI (6739.18±1793), however, significant improvement was recorded in more measures of body composition variables in participants with higher BMI than those with normal BMI. Similarly, significant improvement in biochemical profiles were observed in participants with high BMI on the level of triglycerides (71.62±29.22 to 62.50±29.16 mg/dl, p=0.003) and insulin levels (21.7±8.33 to 18.64±8.25 μU/l, p=0.046) and increase in HMW adiponectin (3.77±0.46 to 3.80±0.44 μg/ml, p=0.034). In conclusion, the prevalence of MetS was 17.5%, being more common in males. HMW adiponectin could play a role in the development of MetS while vitamin D and VDR gene polymorphisms could affect the components of MetS. The participants were “low active”, though perceived more benefits of exercise than barriers. Minimum nominal increase in physical activity can modulate obesity measure, HMW adiponectin and lipid profile with a possible subsequent decrease of cardiovascular risks, particularly in overweight/obese individuals.